Determinants of the success of MSMEs in India: a policy vs. technology perspective. (6th March 2023) - Kumar, Vikas; Nanda, Pooja
The Indian micro, small and medium enterprises (MSMEs) sector is extremely diverse in terms of size, variety of products, service areas, and types of technology being used. It supports the industrial development of rural and backward areas, decreasing provincial discrimination, and ensuring better, unbiased delivery of national revenue and capital. This paper explores the various aspects of the development of MSMEs in India from the perspectives of technology and policy. Specific roles of technology along with domestic and international policies have been analysed to identify their impact on the development of MSMEs. Internet, e-commerce, mobile communication, online payment systems, computer aided designing and social media have been identified as the most important technological determinants of the success of MSMEs. Whereas the impact and provisions of a number of government schemes and initiatives have been presented along with their role in the development of specific categories of MSMEs.